An Efficient Synthesis of 1-Methyl-4,5,6,7-tetrahydro-1H-pyrrolo[2,3-c]pyridine and Its N6-Substituted Analogues - Nechayev, Maxim A.; Gorobets, Nikolay Yu.; Kovalenko, Sergiy M.; Tolmachev, Andrey A. (Synthesis, 2013)
An efficient synthesis of 1-methyl-4,5,6,7-tetrahydro-1H-pyrrolo[2,3-c]pyridine hydrochloride was achieved using simple sodium borohydride reduction of 6-benzyl-1-methyl-1H-pyrrolo[2,3-c]pyridin-6-ium bromide as the key step followed by its debenzylation with hydrogen over palladium on carbon on a multigram scale. Similarly, a series of N6-substituted 1-methyl-1H-pyrrolo[2,3-c]pyridin-6-ium halides were synthesized and reduced with sodium borohydride, showing this method to be applicable for the synthesis of different N6-substituted 1-methyl-4,5,6,7-tetrahydro-1H-pyrrolo[2,3-c]pyridines.
Keywords: heterocycles; cyclization; alkylation; reduction; hydrogenation